Desarrollo de una propuesta para la elaboración de un material para empaques de calzado a partir de un aglomerado compuesto de retazos de cuero y lignina extraída de hojas de maíz (2018)
Of all the industrial sectors that generate high levels of contamination, the agricultural industry and the footwear and leather goods industry were selected to create a strategy that reduces the production of elements alien to the environment by the two sectors. The pieces of rough leather and corn leaves are the waste that was used in this improvement proposal, due to its high production rate. The proposal consists in the creation of a new material, composed of pieces of leather joined by the use of a polymer of natural origin. The biopolymer used is known as lignin, it is one of the most abundant on earth since it is found in the cell wall of plant species and is extracted from the selected maize leaves.